Social Network Analysis: Political Elite Actors #DemokratLawanBegal on Twitter - Susi Nurdinaningsih; Susilo, Daniel; Murwani, Endah (Jurnal Komunikasi Profesional, 2024)
This research explores the impact of the #DemokratLawanBegal hashtag on Twitter, focusing on its role in shaping political discourse and influencing party leaders' alignment. It aims to uncover relationships among elite actors and identify influential figures within the Twitter network using this hashtag. Drawing on concepts like political communication, political elites, Twitter's importance, and Social Network Analysis (SNA), the study adopts SNA methodologies with tools like Netlytic and Gephi Apps. Data collection occurred throughout 3-10 April 2023 to maintain relevance. The findings highlight the significant impact of the #DemokratLawanBegal hashtag in shaping political discourse and the power struggle within the Democratic Party. AHY emerges as a more influential figure than Moeldoko, and Twitter, particularly through this hashtag, plays a central role in political communication and framing strategies. Social Network Analysis reveals a closely interconnected network of actors, with the official Democratic Party account (@pdemokrat) central to information dissemination. Some actors facilitate swift information sharing (closeness centrality), while others serve as key connectors (betweenness centrality). These insights deepen our understanding of contemporary political communication dynamics, offering implications for political campaigns, policy advocacy, and digital strategies.